Action of aluminum on high voltage-dependent calcium current and its modulation by ginkgolide B - Chen Lei; Liu Chang-jin; Tang Ming; Li Ai; Hu Xin-wu; Du Yi-mei; Shen Jing-jing; Lu Yong-li; Heschler Jurgen (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the effect of aluminum (Al) on high voltage-dependent calcium current (IHVA) and its modulation by ginkgolide B (Gin B). Methods: The whole-cell, patch-clamp technique was used to record IHVA from acutely isolated hippocampal CA1 pyramydal neurons in rats. Results: Al 0.1 mmol/L (low concentration) reduced IHVA; Al 0.75 and 1.0 mmol/L (high concentrations) increased IHVA, and Al decreased and increased IHVA at intermediate concentrations of 0.25 and 0.5 mmol/L. The increase of IHVA by Al 1.0 mmol/L was enhanced by the adenylyl cyclase (AC) agonist forskolin and was partly abolished by the cyclic adenosine monophosphate (cAMP)-dependent protein kinase A (PKA) antagonist H-89, whereas the decrease observed with Al 0.1 mmol/L was neither reversed by forskolin nor affected by H-89. Gin B had no effect on IHVA in normal neurons, but canceled the increase in IHVA by 1.0 mmol/L Al. Conclusion: The results indicate that the mechanism of Al affecting IHVA differs at different concentrations, and this may be attributed to its complex actions. Gin B could prevent neurons from injury by inhibiting calcium influx.